Activity Based Costing From the Perspective of Competitive Advantage: A Study of Nigerian Manufacturing Firms - Ebele, Anyadiegwu Peace; Meshach, Ifurueze S. (International Journal of Finance and Accounting, 2016)
Purpose: The focus of this study was to examine activity based costing from the perspective of competitive advantage. ABC can support the strategic management process and provide significant benefit to organizations. This examination utilized the contingency theory as a theoretical basis for the study. Methodology: Descriptive survey design was adopted. The data gathering instrument employed for this study is a structured questionnaire. Data are analyzed through SPSS version 16. Reliability analysis using Cronbach's alpha value was applied on data collected. Factor analysis was employed using principal component method followed by Varimax with Kaiser Normalization, to find the factors or dimensions that explain variances by the data set. The factor analysis is based on four dimensions, namely, overall performance, strategic cost allocation method, increased efficiency and increased effectiveness having the factor loadings of over ±0.3. The regression results are positive and significant at the 5% level. Findings: Findings reveal that there is no statistically significant difference in cost reduction attained by ABC over Traditional costing, though ABC tended to have higher effect. Profits realized in Industrial and Brewery sectors of the Manufacturing companies surveyed were higher in ABC than in Traditional costing. The results further indicated that ABC organizations have higher asset turnover than non-ABC organizations. Also the perception of ABC in terms of strategic cost allocation method increased efficiency, effectiveness and has significant effect on firms' performance. Policy recommendation: This study suggests that the developed scale can have significant implications to capture the perception of ABC. ABC should be applied by manufacturing companies in Nigeria since any little difference in cost - savings can influence managers' decisions.